Three-Dimensional Sound Source Localization by Distributed Microphone Arrays - Adasme-Soto, P (European Signal Processing Conference, EUSIPCO, 2021)
Multiple sound source localization (SSL) is one of the applicable and important areas in the speech signal processing. In this paper, a two-step method is proposed for multiple 3D SSL based on the time delay estimation (TDE) in combination with distributed microphone arrays (DMA). In the first step, the direction of speakers are estimated by the use of a circular microphone array (CMA) in the center of the room and implementing the generalized cross-correlation (GCC) function. In the second step, the distributed T-shaped microphone arrays on the walls are considered for 3D SSL. The two most closed T-shaped array to each speaker are selected, where one of them is used for horizontal and the other one for vertical direction of arrival (DOA) estimation by the use of generalized eigenvalue decomposition (GEVD) algorithm. The experiments on the simulated data for 2 and 3 simultaneous speakers show the superiority of the proposed distributed microphone array-direction of arrival estimators (DMA-DOAE) method in comparison with other previous works in noisy and reverberant environments. © 2021 European Signal Processing Conference. All rights reserved.